Classics of science fiction and fantasy literature - Kelleghan, Fiona, 1965- (Magill's choice., 2002)
"Plot summaries and analyses of 180 major books and series in the fields of science fiction and fantasy ... all but eight of the essays in these volumes are taken directly from Salem Press's four-volume Magill's guide to science fiction and fantasy literature, which was published in 1996"--Publisher's note